Single‐Atom and Subnanocluster Platforms for Next‐Generation Clinical Practice: A Bench‐to‐Bedside Approach - Shrodha Mondal; Prithidipa Sahoo (Chemistry – An Asian Journal, 2026)
ABSTRACT Single‐atom and subnanocluster platforms are at the cutting edge of translational sensing technologies for future clinical use. Their dispersion at the atomic level ensures optimal metal utilization, clearly defined active sites, and precise control over electronic structures. By combining molecular accuracy with solid‐state durability, these materials enhance the adsorption, charge transfer, and catalytic activation of key biomarkers, enabling highly sensitive and selective detection. This review covers recent progress in material design, mechanistic insights, and the integration of these materials into electrochemical and photoelectrochemical diagnostic devices. It also discusses significant challenges related to stability, scalability, and clinical adoption, all of which are crucial for transitioning from laboratory research to real‐world medical applications.